Perfil socioeconômico dos produtores e qualidade do leite produzido na bacia leiteira da microrregião de Pires do Rio(GO) - Cavalcanti, Eliane Resende Costa (2014)
The state of Goiás is the fourth largest milk producer in Brazil, and its South Mesoregion is the leading producer, especially the Micro-region Meia Ponte, southeast of Goiás, Vale do Rio dos Bois and Pires do Rio. Milk quality is one of the factors discussed in this Agroindustrial trade. In 2011.The Ministry of Agriculture, Livestock and Supply (MAPA) published the IN62,in which they established criteria and standards for the production of raw milk. Obtaining good milk quality depends on the first link of the chain, which is the producer. This work was developed with the aim of outlining the socioeconomic profile of the milk producers and the production at the micro-region of Pires do Rio (GO); assessing the impact of IN62/2011 on production systems, making a parallel with the rules through the hygienic quality indicators of health, somatic cell count (SCC) and total bacterial count (TBC) and compositional quality indicators, analyzing the quality of milk and socio- economic-cultural profile of these producers. The data used are came from analyzes previously conducted and the results belong to the file of the Lab Milk Food Research Centre, School of Veterinary and Animal Science, Federal University of Goiás. A structured questionnaire was administered to 86 milk producers of micro-Pires do Rio, on issues regarding socioeconomic information, the use of management techniques related to milk quality and the adequacy of the properties with respect to IN62/2011 resolution SSC and TBC data referring to the period 2011-2012 were tabulated Statistical analysis of the data was used as the experimental unit the milk tank (individual) from which the samples were collected. The date were subjected to non-parametric Kruskal-Wallis test to compare the median values of SCC and TBC of each issue related to milk production in the properties. Significance level of 5% was adopted. Statiscal analyzes were performed using the R software, version 3.0.3. Milk is the main economic activity of the properties,the herds were predominantly of crossbred Girolando, and there was a good technological level in production by the use of mechanical milking machines and tanks expansion. Among the milking procedures, wefound the use of pre - soak in the preparation of the udder. Cows were placed in any order in relation to mastitis and it is preventive treatment of mastitis in dry cows. Operational procedures for cleaning milking equipment are conducted. The results showed that producers are well informed,were of the resolution governing the quality of milk. The degree of impact of IN 62 on their properties was high, due to investments made by the milk producers. Their satisfaction with dairy farming was verified because of their desire to expansion. Higher amounts of fat and protein were observed in the rainy season. Acording to the regulations of the 62/2011 normative, there was significant improvement on milk quality in properties of micro-Pires do Rio-(GO).